The amount of spermatic cord rotation magnifies the time-related orchidectomy risk in Intravaginal testicular torsion - Dias Filho, Aderivaldo Cabral (2016)
Purpose: to investigate the roles of age, testicular rotation and time in the surgical outcome of intravaginal testicular torsion (iTT). Patients and Methods We retrieved the records of all iTT patients treated in our unit from January 2012 to January 2014. Explanatory variables were: age (years); presentation delay (PrD, time between symptoms and hospitalization); surgical delay (SurgD, time between hospitalization and surgery) and testicular rotation (rotation), with surgical outcome (orchidopexy, orchidectomy) as response variable. Differences in PrD, SurgD, age and rotation by surgical outcome were evaluated non-parametrically. Step-down logistic regression included age, PrD, SurgD and rotation as predictors. Statistical significance and confidence intervals (CI) were set at p<0.05 and 0.95. Odds ratios (OR) were computed from the model's coefficients. Results Complete variable information was available for 117 patients, and most (61, 52.1%) underwent orchidectomy. Ages were similar between orchidectomy and orchidopexy patients (median 15.8 vs. 16.0 years, p=0.78). In contrast, PrD (85.0 vs. 8.4 hours, p<0.001), SurgD (3.0 vs. 16.0 hours, p<0.001) were different between orchidectomy and orchidopexy patients. SurgD was similar with PrD<24 hours (4.0 vs. 2.8, p=0.1). Orchidectomy patients had greater rotation (3.0π vs. 2.0π radians, p<0.001). Logistic regression revealed that PrD (OR 0.94; 0.92–0.97; p<0.001) and rotation (OR 0.43; 0.27–0.70; p<0.001) were inversely associated with orchidopexy. Conclusion Testicular rotation exerts a multiplicative effect on PrD, so time should not be regarded as the sole predictor of surgical outcome in iTT.